Prognostic Value of Gamma-Glutamyltransferase in Male Patients With Idiopathic Pulmonary Arterial Hypertension - Lu, Gang-Hua; Gong, Su-Gang; Li, Chao; Zhao, Qin-Hua; Jiang, Rong; Luo, Ci-Jun; Wang, Lan; Zhang, Rui (Frontiers in Cardiovascular Medicine, 2020)
Background: The elevated gamma-glutamyltransferase (GGT) activity is regarded as an indicator of cardiovascular disease, with males having higher values than females. The greater incidence of idiopathic pulmonary arterial hypertension (IPAH) is observed in women, whereas prognosis is poor in men. The present study aims to investigate the potential association of GGT on male patients. Methods: Serum GGT levels were measured in 338 consecutive adult IPAH patients, who underwent bone morphogenetic protein receptor type 2 (BMPR2) genetic counseling, and matched with healthy subjects by sex and age. The followed interval was 48 ± 34 months. Results: Increased serum GGT levels were more common in patients with IPAH than controls (p < 0.001). GGT values were significantly higher in male patients than those of females (p < 0.001). Compared with female patients with BMPR2 mutation, GGT level in male patients with BMPR2 mutation was further increased (p = 0.002). Higher GGT levels were associated with worse hemodynamics and Nterminal pro B-type natriuretic peptide in all patients. However, males with a GGT concentration ≥ 53 U/L had a worse survival than those of females. Contrarily, if GGT concentration <53 U/L, there was no survival difference between male and female patients. After adjustment for relevant variables of clinical features and hemodynamics, baseline higher GGT levels remained increased risks of all-cause mortality in males rather than females. During rehospitalization follow-up, male patients still had significantly higher values of GGT than females. Conclusions: Increased GGT levels were correlated with BMPR2 mutation, hemodynamic dysfunction, and poor outcomes in male patients with IPAH. Further studies are needed to explain the origin of abnormal GGT and its potential pathogenesis in men.